A new potential risk: The impacts of Klebsiella pneumoniae infection on the histopathology, transcriptome and metagenome of Chinese mitten crab (Eriocheir sinensis). Issue 131 (December 2022) - Wang, Chen; Li, Pengfei; Guo, Leifeng; Cao, Hongzhen; Mo, Wei; Xin, Yunteng; Jv, Rong; Zhao, Yun; Liu, Xiaolong; Ma, Changning; Chen, Duanduan; Wang, Hui
Abstract: Klebsiella pneumoniae is a common conditional pathogen found in natural soil water sources and vegetation and can infect invertebrates, vertebrates, and plants. In this study, we isolated K. pneumoniae from the hepatopancreas of the Chinese mitten crab ( Eriocheir sinensis ) for the first time and then we analysed its effects of on the histopathological changes, the transcriptome of the hepatopancreas, and the gut microbiota of this crab species. The findings of this study showed that K. pneumoniae infection has led to significant structural changes in the hepatopancreas, such as the production of vacuolated tissue structures, disorganized cell arrangement, and lysis of some hepatopancreatic cells. Also, the infection caused activation of the antioxidant-related enzymes such as SOD and CAT by inducing oxidative stress. The transcriptome of the hepatopancreas identified 10, 940 differentially expressed genes (DEGs) in the susceptible (SG) groups and control (CG) groups, and 8495 DEGs in the SG groups and anti-infective (AI) groups. The KEGG pathway revealed upregulated DEGs caused by K. pneumoniae infection that involved in the immune response and apoptotic functional pathways, and also downregulated DEGs involved in the digestive absorption, metabolic, and biosynthetic signaling pathways. Meanwhile, metagenics sequencing revealed that at the phylum, class, order, family, and genus levels, K. pneumoniae infection altered the composition of the gut microbiota of E. sinensis, through increasing the abundance of Prolixibacteraceae, Enterobacterales, and Roseimarinus and decreasing the abundance of Alphaproteobacteria . The flora structure has also been changed between the SG and AI groups, with the abundance of Firmicutes, Erysipelotrichales, and Erysipelotrichaceae that were significantly decreased in the SG groups than in the AI groups. But, the abundance of Acinetobacter was considerably higher than in the AI group. In summary, K. pneumoniae infection induced oxidative stress in E. sinensis, triggered changes in immune-related gene expression, and caused structural changes in the gut microbiota. This study provides data to support the analysis of bacterial infection probes in several crustacean species. Highlights: K. pneumoniae K57 can infect E. sinensis and leads to hepatopancreatic vacuolation. RNA transcriptome has been changed during K. pneumoniae infection in E. sinensis hepatopancreas. K. pneumoniae infection affects the gut microbiota structure of E. sinensis.